Presence of patent foramen ovale does not increase cerebrovascular event rates in patients with atrial fibrillation following left atrial appendage closure - Chunyu Chen; Li Liu; Yonghua Zhang; Dan Chen; Yuyi Chen; Lulu Qu; Xi Su; Yanhong Chen (Heliyon)
Objective: Both atrial fibrillation (AF) and patent foramen ovale (PFO) has been associated with occurrences of ischemic stroke. The aim of this study was to investigate whether patients with concomitant AF and PFO were at an increased risk of stroke, and whether PFO closure was necessary for the prevention of stroke in AF patients who underwent left atrial appendage closure (LAAC). Method: We retrospectively analyzed 614 patients who underwent LAAC at Wuhan Asia Heart Hospital from May 2014 to April 2021. We compared the baseline clinical characteristics and ischemic stroke rates before LAAC, major adverse cardiovascular events (MACEs) and other long-term outcomes between AF patients with and without PFO after LAAC. The predictor for ischemic stroke or TIA after LAAC was analyzed with univariate and multivariable Cox regression, and the long-term cumulative survival rates of AF patients with PFO compared to those without PFO after LAAC were analyzed with the Kaplan–Meier graph. Results: A total of 614 patients who underwent LAAC and had completed follow-up data were included in our study. Among them, 74 patients were diagnosed with AF with PFO, and 540 with AF without PFO. There was no significant difference between their baseline clinical data, including ischemic stroke rates (p = 0.961). Patients with and without PFO had similar device implantation success rates (98.6 % vs 99.4 %, P = 0.403) and procedure-related complications. During follow-up (medium follow-up period 36.9 months), no significant difference was observed in the incidence of MACEs (8.1 % in PFO group vs 5.7 % in non-PFO group, P = 0.432) or the cumulative ischemic stroke/TIA rates (5.4 % in PFO group vs 4.3 % in non-PFO group, P = 0.554). The Cox multivariable regression analysis indicated that the presence of PFO in patients with AF had no correlation with ischemic stroke or TIA after LAAC implantation (HR 1.685, 95 % CI 0.570–4.978, P = 0.345). The only predictor for ischemic stroke/TIA events after LAAC was major leakage (>5 mm) seen on transesophageal echocardiography (TEE) or left atrial CTA at the 45-day follow-up (HR 10.352, 95 % CI 1.221–87.736, P = 0.032). Conclusion: AF patients with PFO are not at increased risk for ischemic stroke or TIA before LAAC. The presence of PFO in AF patients did not affect the success rate and safety of LAAC. The presence of mild PFO is not a viable predictor of stroke events in AF patients who underwent LAAC during long-term follow-up. Major leakage (>5 mm) is associated with a higher ischemic stroke/TIA rate in AF patients who underwent LAAC.